Coastal aquaculture farms for the sea cucumber Apostichopus japonicus provide spawning and first-year nursery grounds for wild black rockfish, Sebastes schlegelii: A case study from the Luanhe River estuary, Bohai bay, the Bohai Sea, China - Xu, Min; Qi, Zun-li; Liu, Zun-lei; Quan, Wei-min; Zhao, Qi; Zhang, Yun-ling; Liu, Hui; Yang, Lin-lin (Frontiers in Marine Science, 2022)
Aquaculture farms are known to attract wild organisms from nearby areas. Sea cucumber Apostichopus japonicus aquaculture farms in Bohai Bay, the Bohai Sea, China, might provide spawning and nursery grounds for wild black rockfish Sebastes schlegelii populations. To identify the above, we studied the variation in the numbers of S. schlegelii larvae (and length-categories as a percentage of the natural population) via ichthyoplankton surveys by months from January to October 2020, and assessed the food web structure and energy flow distribution of the farm and trophic links of S. schlegelii natural stock by using Ecopath modeling in July 2016 to August 2017. Larvae with a length between 3.90-5.80 mm were observed in the farm in May 2020, the juveniles with an estimated trophic level of 4.31. Juveniles used the farms as first-year nursery ground, and then they swam into deeper waters in August of the following year. MTI analysis showed increasing biomass of S. schlegelii might result in a decrease in the biomass of crustacea, and had positive and negative impacts on mollusk and Hexagrammos otakii biomass. We argued that aquacultural infrastructures constructed by artificial reefs could be used as a fisheries management tool to enhance S. schlegelii stocks and that monitoring of other marine organisms, such as oysters, Rapana venosa, Charybdis japonica, and Asterias spp. etc., was necessary to maintain sustainable exploitations of aquacultural farm ecosystems. A paucity of knowledge surrounding the interactions between aquaculture farms and wild organisms needs furthermore researches.